ДИНАМИКА КАЧЕСТВЕННЫХ ХАРАКТЕРИСТИК АДМИНИСТРАТИВНО0ПОЛИТИЧЕСКОЙ ЭЛИТЫ СРСР В “ЭПОХУ” Л.И. БРЕЖНЕВА: ИСТОРИКО0 ПОЛИТИЧЕСКИЙ АНАЛИЗ (Zaporizhzhia Historical Review, 2021)
The author analyzes socio-structural (quality) characteristics of local politicaladministrative elite of Tambov region of Russian Soviet Federal Socialist Republic (RSFSR) in 1965-1982s. Such characteristic features of municipal and district Soviet Union Communist Party committees’ secretaries as age, education, beginning of labor activity, Party membership period are highlighted. The conclusion is drawn that in 1970s at the regional level is established such Party official as technocrat, who focuses on knowledge, acquired in university and not upon ideological dogmas.